Global, regional, and national burden of ovarian cancer attributable to high body mass index, 1990–2021: insights from the global burden of disease study 2021 - Wang, Yinghua; Yu, Yuexin (Frontiers in Oncology, 2025)
ObjectiveBuilding on established evidence linking excess body fatness to increased risk of ovarian cancer, this research aims to assess the global and regional disease burden of ovarian cancer attributable to high body mass index (BMI) from 1990 to 2021 using data from the Global Burden of Disease (GBD) study. Here, we specifically focus on quantifying trends in age-standardized mortality rates (ASMR) and age-standardized disability-adjusted life year rates (ASDR) to elucidate evolving epidemiological patterns and regional disparities.MethodsComprehensive data were extracted from the GBD 2021 database to analyze trends in ASMR, ASDR, absolute deaths, and disability-adjusted life years (DALYs) attributable to high BMI-related ovarian cancer from 1990 to 2021, stratified by global, regional, and socio-demographic index (SDI) quintiles. The key methodological approaches included Joinpoint regression analysis to identify significant temporal changes in ASMR and ASDR trends and correlation analysis to determine associations between disease burden (ASMR/ASDR) and SDI. Additionally, future projections for ASMR and ASDR burdens from 2022 to 2050 were generated using a Bayesian Age-Period-Cohort (BAPC) framework, accounting for demographic shifts and inherent uncertainties.ResultsBetween 1990 and 2021, global ASMR and ASDR for ovarian cancer attributable to high BMI remained relatively stable. However, the absolute number of deaths and DALYs increased substantially over this period. ASMR and ASDR exhibited a strong positive correlation with SDI, with the highest burden observed in regions with SDI values between 0.7 and 0.8. While high-SDI regions experienced the greatest burden in both 1990 and 2021, an overall declining trend was observed. Conversely, regions across other SDI quintiles exhibited an increasing burden. BAPC projections suggest a continued global increase in the ovarian cancer burden attributable to high BMI, with global ASMR projected to reach 1.64 (95% uncertainty level (UI): 1.35–1.93) and ASDR to reach 54.63 (95% UI: 45.41–63.84) by 2050.ConclusionThis study highlights persistent and significant regional disparities in the ovarian cancer burden attributable to high BMI, strongly associated with SDI, and projects a concerning increase in the future global burden. Our collective findings underscore the urgent need for targeted and proactive interventions to mitigate the impact of high BMI on ovarian cancer outcomes worldwide.